Webinar Education for High School Students: What Major to Choose for University - Renna Magdalena; Tanggor Sihombing; Ilyona Risty; Go George Herbert; Josephine Kurniawati Tjahjono; Gloria Mariana Kristanti Harjanto (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
Lecturers of the Faculty of Economics and Business, Pelita Harapan University, carried out this service activity. This activity is worth doing because many high school students need help understanding what they will face in college. One of the main challenges prospective students face is choosing the right major according to their interests, talents, and career goals. These decisions will have a long-lasting impact on a person's personal and professional development. This service activity is expected to provide prospective students with knowledge and understanding about the majors needed in the current era. The goal is to provide an understanding of what the students need as prospective students to step into the world of lectures with suitable and appropriate majors.